An argumentation-based negotiation for distributed extended logic programs - Almeida, Iara (2012)
The paradigm of argumentation has been used in the literature to assign meaning to knowledge bases in general, and logic programs in particular. With this paradigm, rules of a logic program are viewed as encoding arguments of an agent, and the meaning of the program is determined by those arguments that somehow (depending on the specific semantics) can defend themselves from the attacks of other arguments. Most of the work on argumentation-based logic programs semantics has focused on assigning meaning to single programs. In this paper we propose an argumentation-based negotiation semantics for distributed knowledge bases represented as extended logic programs that extends the existing ones by considering sets of (distributed) logic programs, rather than single ones. For specifying the ways in which the various logic programs may combine their knowledge we make use of concepts that had been developed in the areas of defeasible reasoning, distributed knowledge bases, and multi-agent setting. In particular, we associate to each program P a cooperation set (the set of programs that can be used to complete the knowledge in P) and the argumentation set (the set of programs with which P has to reach a consensus).